The Role of Ease of Use, Usefulness, Trust, and Algorithms in Platform Choice Among Batam Content Creators - Willson; Eryc; Surya Tjahyadi (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2025)
This research examines how Perceived Ease of Use, Perceived Usefulness, Perceived Trustiness, and Algorithm Awareness influence the attitude and intention of Batam content creators in utilizing digital platforms. Data collected from 137 Batam content creators were analyzed using linear regression. Results indicate that Perceived Ease of Use significantly affects Perceived Usefulness (t = 6.007, p < 0.001), but neither Perceived Ease of Use (t = 0,315, p = 0.753) nor Perceived Usefulness (t = 1.664, p = 0.099) impacts attitude. In contrast, Perceived Trustiness (t = 4.109, p < 0.001) and Algorithm Awareness (t = 2.584, p = 0.011) positively influence attitudes, while a strong relationship exists between attitude and intention to use platforms (t = 8.654, p < 0.001). These findings suggest that content creators should understand algorithm functionality and use trusted platforms to enhance content visibility and audience reach. Platform developers should focus on building trust by ensuring data security, transparent and fair content distribution systems, to create a sense of reliability & trustworthy, encouraging Batam creators to use the platform more actively.